2009
DOI: 10.4049/jimmunol.182.3.1253
|View full text |Cite
|
Sign up to set email alerts
|

ISCOMATRIX Adjuvant Induces Efficient Cross-Presentation of Tumor Antigen by Dendritic Cells via Rapid Cytosolic Antigen Delivery and Processing via Tripeptidyl Peptidase II

Abstract: D endritic cells (DC)3 are highly specialized APCs that take up exogenous material from the extracellular environment for presentation in the context of MHC molecules. Next to presentation of antigenic epitopes on MHC class II molecules to CD4 ϩ T cells, DCs can also shuttle Ag to the MHC class I processing pathway for CD8 ϩ T cell activation, a process termed crosspresentation (reviewed in Ref. 1). This enables DCs that have engulfed tumor Ag to activate Ag-specific CD8 ϩ T cells capable of tumor cell killing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 38 publications
3
77
1
Order By: Relevance
“…4,38,39 We found that proteasome inhibition significantly reduced NY-ESO-1 157-165 / HLA-A2, NY-ESO-1 60-72 /HLA-B7, and NY-ESO-1 92-100 /HLA-Cw3-restricted cross-presentation when NY-ESO-1 was presented as an IC (Figure 7). In contrast, proteasome inhibition had no effect on the generation of either the NY-ESO-1 157-165 /HLA-A2 or NY-ESO-1 92-100 /HLA-Cw3 epitopes but dramatically inhibited NY-ESO-1 60-72 /HLA-B7 epitope generation, either when DCs were exposed to formulated NY-ESO-1/ISCOMATRIX vaccine or when NY-ESO-1 and ISCOMATRIX adjuvant were added separately to the DCs ( Figure 7).…”
Section: Dcs Use Proteasome-dependent and -Independent Mechanisms Formentioning
confidence: 86%
See 4 more Smart Citations
“…4,38,39 We found that proteasome inhibition significantly reduced NY-ESO-1 157-165 / HLA-A2, NY-ESO-1 60-72 /HLA-B7, and NY-ESO-1 92-100 /HLA-Cw3-restricted cross-presentation when NY-ESO-1 was presented as an IC (Figure 7). In contrast, proteasome inhibition had no effect on the generation of either the NY-ESO-1 157-165 /HLA-A2 or NY-ESO-1 92-100 /HLA-Cw3 epitopes but dramatically inhibited NY-ESO-1 60-72 /HLA-B7 epitope generation, either when DCs were exposed to formulated NY-ESO-1/ISCOMATRIX vaccine or when NY-ESO-1 and ISCOMATRIX adjuvant were added separately to the DCs ( Figure 7).…”
Section: Dcs Use Proteasome-dependent and -Independent Mechanisms Formentioning
confidence: 86%
“…For NY-ESO-1, this may have been in association with cell surface calreticulin, as previously described, 43 which had been internalized into endosome/phagolysosomal compartments. 38 Similar mechanisms may apply for Melan-A, even though cell surface binding with calreticulin has not been described. As previously shown, the addition of ISCOMATRIX likely facilitates translocation into the cytosol, thereby providing tumor antigen access to the class I MHC pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations